Charismatic, competent or transformative? Ontario school administrators' perceptions of "good teachers" - Laura Elizabeth Pinto; John P. Portelli; Cindy Rottmann; Karen Pashby; Sarah Elizabeth Barrett; Donatille Mujawamariya (University of Windsor, 2012)
Emphasis on issues of social justice and attention to socio-cultural perspectives on learning might be at odds with prevailing conceptions of "the good teacher." In this paper, we probe the perceptions of "good teaching" among Ontario school administrators. We begin with an investigation into dominant discourses of "good teachers" based on the framework posited by Moore (2004). Next, we examine the context that gave rise to Ontario's New Teacher Induction Program (NTIP), and how this program shapes perceptions of good teachers and good teaching. Data from interviews with forty-one school administrators shed light on their perspectives on good teachers, which is analyzed in light of the dominant discourses and the governing NTIP policy and practice. The discussion highlights the highly personal nature of perceptions of good teaching, and ways in which Ontario school administrators' perceptions tend to reinforce dominant discourses. The conclusion raises questions about how new teacher induction programs reinforce dominant discourses, and raises possibilities to allow for alternate discourses to coexist.